2013
DOI: 10.1177/1757975913499035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public expenditure on undernourishment distribution in Mexico

Abstract: The status of undernourishment in children under the age of five in Mexico is open to debate. Linked to poverty, underweight and stunting, the rates of undernourishment are reported to be diminishing, although poverty remains an incessant problem. This study was done to determine whether there is an association between public expenditure and underweight and stunting distribution in Mexico based on data from the 2006 health and population census and from macroeconomic, social, and demographic variables. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…The possibility of more allocation of health funds is directed to alleviate diseases and still very little to fulfill children's nutrition. Then, GDP per capita shows the results of estimates that have not affected the betterment of children's chronic malnutrition, and this confirms previous studies that found that increased public spending aimed at combating malnutrition is not predominantly targeted to meet the needs of the inferior [9]. The estimated GDP per capita of districts/cities in this study shows that regardless of the areas with low and high GDP, the prevalence of stunting remains.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…The possibility of more allocation of health funds is directed to alleviate diseases and still very little to fulfill children's nutrition. Then, GDP per capita shows the results of estimates that have not affected the betterment of children's chronic malnutrition, and this confirms previous studies that found that increased public spending aimed at combating malnutrition is not predominantly targeted to meet the needs of the inferior [9]. The estimated GDP per capita of districts/cities in this study shows that regardless of the areas with low and high GDP, the prevalence of stunting remains.…”
Section: Plos Onesupporting
confidence: 87%
“…No research has studied the role of political economy factors in stunting prevalence, especially in Indonesia. The government's role is highly required to prevent stunting [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil yang didapat dari penelitian-penelitian tersebut sangat beragam, tergantung jangka waktu dan karakteristik wilayah intervensi dilakukan. Kajian intervensi gizi spesifik terkait asupan zat gizi balita juga menemukan bahwa makanan dengan kandungan zat gizi makro maupun zat gizi mikro juga menentukan probabilitas anak mengalami stunting atau tidak (Ahmed et al, 2012;Fahmida et al, 2020;Moreno-Macías et al, 2013;Nachvak et al, 2020). Begitu pula dengan pola asuh ibu dan praktik pemberian ASI yang berperan besar dalam penentuan status gizi anak (Beal et al, 2018;Stewart et al, 2013).…”
Section: Pendahuluanunclassified
“…Beberapa studi empiris telah dilakukan untuk menganalisis dampak pemberian intervensi gizi terhadap penurunan risiko stunting, baik intervensi gizi spesifik yang menyasar dampak langsung stunting maupun intervensi gizi sensitif yang menyasar dampak tidak langsung stunting. Kajian intervensi gizi spesifik terkait asupan zat gizi balita juga menemukan bahwa makanan dengan kandungan zat gizi makro maupun zat gizi mikro juga menentukan probabilitas anak mengalami stunting atau tidak (Ahmed et al, 2012;Fahmida et al, 2020;Kaimila et al, 2019;Moreno-Macías et al, 2013;Nachvak et al, 2020;Ssentongo et al, 2020). Begitu pula dengan pola asuh ibu dan praktik pemberian ASI yang berperan besar dalam penentuan status gizi anak (Beal et al, 2018;Stewart et al, 2013).…”
Section: Tinjauan Empiris Kebijakan Intervensi Gizi Dan Prevalensi St...unclassified